Observer-based PID control for actuator-saturated systems under binary encoding scheme - Wen, Pengyu; Dong, Hongli; Huo, Fengcai; Li, Jiahui; Lu, Xuqing (Neurocomputing (Amsterdam), 2022)
In this paper, the observer-based proportional-integral-derivative (PID) control problem is investigated for a class of actuator-saturated systems affected by multiplicative noises under the binary encoding scheme (BES). The communication between the sensors and the observers is implemented via a shared network, in which the measurement signals are transmitted by the BES. During the transmission, random bit errors may occur in the bit string due to the channel noises. The aim of this paper is to design an observer-based PID controller such that the closed-loop system is exponentially mean-square ultimately bounded with the consideration of random bit errors, actuator saturations and multiplicative noises. Sufficient conditions are presented to guarantee the expected performance of the resulted tracking error, and the controller gain matrices are obtained by solving a set of matrix inequalities. Finally, the effectiveness of the proposed PID control scheme is verified by a simulation example.